Pengaruh Pemberian Buah Pisang Mas Terhadap Peningkatan Kadar Hb Pada Ibu Hamil Trimester III - Elsa Kumala Safitri; Miftahul Mualimah; Herliana Riska (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2019)
Hemoglobin is a protein-rich substance bezi, Have affinity (power team) against oxygen and with oxygen it forms a oxihemoglobin in red blood cells. The goal in this research is to know the influence of banana fruit mas to increased hemoglobin on pregnant women trimester III in BPM Ny